2017
DOI: 10.1038/ncomms14857
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of the viscoelastic properties of vinylogous urethane vitrimers

Abstract: Vinylogous urethane based vitrimers are polymer networks that have the intrinsic property to undergo network rearrangements, stress relaxation and viscoelastic flow, mediated by rapid addition/elimination reactions of free chain end amines. Here we show that the covalent exchange kinetics significantly can be influenced by combination with various simple additives. As anticipated, the exchange reactions on network level can be further accelerated using either Brønsted or Lewis acid additives. Remarkably, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
392
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(408 citation statements)
references
References 28 publications
16
392
0
Order By: Relevance
“…[1,29,30] To better explain the distinction between these two classes of dynamic networks, it must be reminded that reversible reactions controlled by chemical equilibria are defined by two parameters: the rate of exchange and the balance of species determined by an equilibrium constant through the law of mass action. This comes as a complete contrast to other vitrimers that are specifically defined and differentiated from conventional covalent adaptable networks (CANs) by the nondissociative nature of their bond exchange.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,29,30] To better explain the distinction between these two classes of dynamic networks, it must be reminded that reversible reactions controlled by chemical equilibria are defined by two parameters: the rate of exchange and the balance of species determined by an equilibrium constant through the law of mass action. This comes as a complete contrast to other vitrimers that are specifically defined and differentiated from conventional covalent adaptable networks (CANs) by the nondissociative nature of their bond exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the functionality of the reactants, deviation from the stoichiometry in these systems can have severe consequences on the structure of the network, ultimately leading to branched oligomers instead of covalently cross-linked polymer networks. Such range of ratios ensures that all networks are strongly cross-linked (note that for z = 1, there are as many alkyl iodide than N-alkylable 1,2,3-triazole groups) while enabling considerable variation in the chemical composition of the networks, theoretically covering three cases: preponderance of bis-1,2,3-triazolium cross-links (2T + ) for z = 1, preponderance of 1,2,3-triazole segments (T) for z ≪ 1, or preponderance of [1,6,14,25,[28][29][30] iodide-functionalized dangling chains (IT + ) as well as unreacted cross-linker (2I) for z ≫ 1 (Figure 2). [32] These poly(1,2,3-triazole) chains with considerable functionality are cross-linked in situ by N-alkylation reaction between 1,2,3-triazole units and a difunctional cross-linker such as diodooctane 2I.…”
Section: Monotopic Generation Of Ptil Ionic Vitrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence of the stress relaxation is illustrated in Figure B for cured p X2.4 and it is immediately clear that an increase in temperature leads to a faster stress relaxation. Analogous to what has been done in other vitrimer studies, we use the relaxation time τ, which is defined as the time it takes for the modulus to relax to 1/e of its original value, as a characteristic measure for stress relaxation. The data in Figure B show that an increase in temperature from 230 to 260 °C leads to a decrease in τ from 5 × 10 3 s to 3 × 10 2 s. The effects of BPO content and debenzalation strategies are shown in Figure C.…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated that the crosslinking Diels–Alder reaction between anthracene and maleimide moieties can be used to achieve healing efficiencies . Polyimine is a new type of thermoset vitrimer material with unique properties such as self‐healing, recyclability, and environmental friendliness due to dynamic‐covalent interaction of imine bonds . Polyimine can be conveniently processed by heat‐pressing at ambient conditions and self‐healed at ambient temperature using water.…”
Section: Introductionmentioning
confidence: 99%